CRITICAL REVIEW OF HEALTH INFORMATICS TECHNICIAN TRAINING PROGRAMS IN ASSESSING CURRICULUM AND SKILLS DEVELOPMENT - 1MOHAMMAD HAMAD MOHAMMAD ALYAMI, 2YUOSEF SALEM MOHAMMED ALYAMI, 3SALEM HASSAN RASHED ALMANSOUR, 4SALEH MANA SALEH ALHUTAYLAH, 5NASSER MAHDI NAQTAN AL SIWAR, 6ALI SALEM NASSER AL ABBAS, 7ALI YAHYA MOHAMMED ALZUBAIDI, 8SULTAN ALI HUSSEIN ALYAMI (Chelonian Research Foundation, 2022)
Health informatics technician training programs are vital for equipping professionals with the skills necessary to navigate the rapidly evolving landscape of healthcare. This critical review looks at the curriculum and the improvement of abilities in these subjects, employing a comprehensive approach that incorporates writing review and methodological audit, as well as the discoveries of different ponders. This article aims to assess the viability of current preparation programs and distinguish ranges for change. The sessions investigated the quality of curriculum advancement and tended to find holes in curriculum design and aptitude improvement. The extreme objective is to guarantee that graduates are arranged to succeed within the healthcare industry and have the information and aptitudes fundamental to adjust patient care and vital records to constantly changing conditions deliberately and compellingly. Keywords:health informatics, technician training programs, curriculum assessment, skills development.